KONSEPSI GURU MODERN DALAM PENDIDIKAN ISLAM - Sarno Hanipudin (Institut Agama Islam Imam Ghozali, 2020)
Education represent major capital to increase excellent human resource of a nation. Teacher is the most determining factor to reach the education excellence. Islam has emphasized the importance of human resource excellence, and the importance of education excellence to reach victorius live. Therefore, Islam place teacher as determinant key factor of education success, as practiced by Rasulullah as teacher with the feature that recently marked as modern teacher’s features.